Retiring from Intercollegiate Athletics: A Phenomenological Investigation - Muccio, Douglas J.; Hector, Mark A. (My University, 2005)
The major objective of this research was to explore the experience of retiring from sport following a career in college athletics. The phenomenological method was used to interview five retired athletes and gather data, A clearer understanding of the experience of the participant is established by the unstructured interview style inherent within the phenomenological method, allowing the participant to control the interview and be the expert of his or her own experience. Following these interviews, a research group analyzed the transcripts looking for themes that existed for all five participants. Four main themes with subthemes emerged from this analysis, including Identity, with the sub-themes of Void, Emotion, and Life Shift/Redirection; The Game, with the subthemes of Stories of Past History, Difference between Levels of Sport, Contentment in Reminiscing, and Retirement as a Process; Body, with the subthemes of Fitness/Being in Shape, Injury, and Speed; and Others, with the subthemes of The Team (Coaches/Teammates) and The Community (Family/Friends). It is the hope of the author that this research will provide a clearer understanding of the experience of retiring from sport so that coaches, parents, counselors, and the athletes themselves can take steps toward having a successful and constructive retirement.
Keywords: identity; transitions; injury